Konstruksi Pasal 33 UUD 1945 dalam Menangkal Pengaruh Sistem Kapitalisme di Indonesia - Ashabul Fadhli; Recy Harviani Zurwanty; Vivi Puspita Sari (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2023)
It is undeniable that the grip of capitalism has been rooted in Indonesia since colonialism, independence to the development of today's globalization. The roots of capitalism in Indonesia have hindered the achievement of the objectives of implementing independence in terms of improving the economic welfare of the people. This can be seen in the Investment Law with its transfer and repatriation system which makes it easier for foreign companies to transfer their profits abroad, the plantation sector which is more profitable for large companies, the retail market which has begun to enter rural areas and the principle of developmentalism which allows large debts to international institutions. In order to strengthen the goal of independence, and to avoid the influence of capitalism which can undermine the stability of the national economy and social welfare, a deeper study of Article 33 of the 1945 Constitution is needed. This research departs from normative legal research. The approach used is a legal-statutory approach and a historical approach. The results of this study prove that the 1945 Constitution has a very strong influence in determining the national economic system. Conducting a review of Article 33 of the 1945 Constitution is important so that the State with its powers in realizing the greatest prosperity and welfare of society.